Recommendations for athletes and COVID-19 vaccinations: A South African Sports Medicine Association (SASMA) position statement – Part 3 - Pillay, Lervasen; Patricios, Jon; Janse van Rensburg, Dina Christa; Saggers, Robin; Ramagole, Dimakatso; Viviers, Pierre; Thompson, Craig; Hendricks, Sharief (South African Journal of Sports Medicine, 2021)
The COVID-19 pandemic initially led to the shutdown of all sport at a high cost to both the economy and athlete health. As risk-mitigating protocols evolved and were implemented, the playing of sport returned slowly to normal. The introduction of COVID-19 vaccinations enhances the means of protection and risk management for all. This South African Sports Medicine Association position statement provides recommendations for the vaccination of athletes.